PERTANGGUNGJAWABAN PRESIDEN BERDASARKAN SISTEM KETATANEGARAAN PASCA AMANDEMEN UUD NRI 1945 - Hidayat, Rosalinda Geeta Sakavati; Sudibya, Komang Pradnyana (Kertha Desa, 2024)
Maksud studi tulisan ini guna mengkaji perbahasan pertanggungjawaban Presiden yang perlu disampaikan secara gamblang dan efektif dalam UUD NRI 1945, terpenting pasca amandemen. Pertanggungjawaban Presiden pasca amandemen UUD NRI 1945 merupakan pertanggungjawaban yuridis berdasarkan sistem pemerintahan yaitu berupa wujud pelanggaran hukum bentuk pidana dan perbuatan pidana lainnya selama masa jabatannya. Hal ini diperlukan dengan maksud apa yang dipertanggungjawabkan dalam pemerintahan dengan sanksi yang maksimum yaitu pemberhentian dari masa jabatan secara tidak terhormat. Guna mendalami itu lanjutnya, perlu dilakukan penelitian mendalam. Tujuan dari penulisan ini adalah bertautan dengan pertanggungjawaban Presiden di Indonesia mengikuti UUD NRI 1945. Wujud dan prosedur pertanggungjawaban Presiden berdasar UUD NRI 1945. Proses metode dalam penulisan ini yakni pendekatan yuridis preskriptif normatif dengan akumulasi bahan hukum melalui proses rekognisi bahan-bahan hukum pokok dan bahan-bahan hukum lainnya. Penulisan ini juga memberikan penulisan deskriptif mengenai pelaksanaan fungsi pengawasan DPR terhadap Presiden dalam menjalani tugasnya. The purpose of this paper is to examine the debate on the responsibility of the President that needs to be conveyed clearly and effectively in the 1945 Constitution of the Republic of Indonesia, most importantly after the amendment. The accountability of the President after the amendment of the 1945 Constitution of the Republic of Indonesia is a juridical accountability based on the government system, namely in the form of a form of violation of the law of criminal form and other criminal acts during his term of office. This is necessary with the intention of what is accounted for in government with maximum sanctions, namely dismissal from office dishonorably. In order to explore it, it is necessary to conduct in-depth research. The purpose of this paper is related to the accountability of the President in Indonesia following the 1945 Constitution of the Republic of Indonesia. The form and procedure of the President's accountability based on the 1945 Constitution of the Republic of Indonesia. The method process in this writing is a normative prescriptive juridical approach with the accumulation of legal materials through the process of recognition of basic legal materials and other legal materials. This writing also provides descriptive writing about the implementation of the DPR's supervisory function towards the President in carrying out his duties.